ダイ21ジ ナンキョク チイキ カンソク タイ キスイケン ブモン カンソク ガイホウ 1980 - 小林, 俊一; コバヤシ, シュンイチ; 石川, 信敬; イシカワ, ノブヨシ; 大畑, 哲夫; オオハタ, テツオ; 川口, 貞男; カワグチ, サダオ; Kobayashi, Shun'ichi; Ishikawa, Nobuyoshi; Ohata, Tetsuo; Kawaguchi, Sadao (1982)
P(論文) 1979年(第20次隊)から3年計画の南極の極域気水圏観測計画(POLEX-South)が開始され, みずほ基地で放射および接地気層の精密観測が行われた。1980年度(第21次隊)は, みずほ基地で接地逆転層や斜面滑降風の構造の研究のために(1) 30m観測塔による大気境界層観測(2)放射収支観測(3)低層ゾンデ観測(4)音波レーダ観測(5)超音波風速温度計による顕熱輸送量測定(6)飛雪の観測(7)超音波式積雪深計による雪の堆積量変化の測定(8)定常気象観測を行った。他方昭和基地周辺では(1)海氷上の熱収支とパドルの形成機構の研究(2)音波レーダ観測(3)無人気象観測(4)航空機による日射・表面温度・雪面形態・マルチバンドカメラ観測(5)水中氷の観察を行った。以上の観測の測器, 測定法, 観測経過, 得られた主な成果, 今後の問題点について述べた。 In 1980,the present authors in the 21st Japanese Antarctic Research Expedition carried out glacial-meteorological observations at Mizuho Station and Syowa Station as the second year programme of the Japanese POLEX-South. Items of observation at Mizuho Station (70°42′S, 44°20′E, 2230m above sea level) were : 1) observations of surface boundary layer by a 30m high observation tower, 2) radiation budget, 3) low level radio-sondes, 4) sonic-wave sounder, 5) measurements of sensible heat flux by sonic-anemometer, 6) blowing snow, 7) snow accumulation by sonic-wave snow depth meter and 8) surface synoptic weather. In the vicinity of Syowa Station (69°00′S, 39°35′E, on East Ongul Island), the following studies were carried out : 1) heat budget of sea ice, 2) observation of surface inversion layer by sonic-wave sounder, 3) meteorological observations by an unmanned weather station, 4) airborne survey of radiation budget, surface radiation temperature and surface morphology, and 5) observations of frazil ice. This paper mainly describes the installation and performance of the measurement system and preliminary results. departmental bulletin paper